Problematika Klaim Nasabah Asuransi Jiwa Syariah di PT. Prudential Life Assurance Unit Prestasi Agency Binjai - Dini Dwi Ariska; Yusrizal (Universitas Muhammadiyah Surabaya, 2023)
Abstract Life insurance is insurance that aims to protect someone against unexpected financial losses due to death. The problems that occur at PT. Prudential Life Assurance Agency Binjai, namely the rejection of customer claims. The causes of rejected customer claims are because customers do not complete the requirements and claim submission documents, illnesses claimed are not covered by the company, inactive insurance policies, dishonesty in disclosing medical history, claims are included in exceptions, and the claim filing period has passed the expiration date. In addition, there are 4 things that cause sharia life insurance cannot be claimed by customers who have died, namely death by suicide, being sentenced to death in court, fights, demonstrations, and being killed by enthusiasts or their relatives in order to get compensation. To avoid being rejected by customer claims, the insured should complete the specified documents and follow the procedures for submitting predetermined claims, such as policies, KTP PP, KTP TU, KTM PM, receipts for hospital fees, doctor's certificates, death certificates, claim forms, and other required documents. In this study using descriptive qualitative method with data collection using observation and interviews to obtain valid information. Keywords: Problems, Life Insurance, Denial of Claims